From public reason to multi-layered justice - Ben Crum (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
This paper seeks to lay out a theory of multi-layered political obligations that, on the one hand, allows for their projection to the international level and, on the other hand, recognizes the privileged status of the nation-state. To arbitrate between the range of the duties that can be imposed at the different levels, I adopt the Rawlsian concept of public reason to submit that duties of justice can only be imposed to the extent that the actors involved command a shared set of reasons by which these can be justified. The paper's argument follows Rawls in using public reason to justify a qualitative distinction between the demands that derive from the domestic and the international domain of justice. It criticizes Rawls, however, for misjudging the radical implications of this position in a world that has become much more internationalized than he recognized it to be. This empirical critique paves the way for a multi-layered conception of justice in an internationalizing world that is based on the effective operation of public reason. This discussion paper is part of a series of contributions to the conference "Towards a Grammar of Justice in EU Law', which took place on 6-7 November 2014 at VU University Amsterdam, sponsored by Amsterdam, VU Centre for European Legal Studies and the Dutch Research Council VENI grant.
Keywords: 320; multi-layered political obligations; nation-state; public reason